2016
DOI: 10.1158/2159-8290.cd-15-0283
|View full text |Cite
|
Sign up to set email alerts
|

Loss of PTEN Promotes Resistance to T Cell–Mediated Immunotherapy

Abstract: T cell-mediated immunotherapies are promising cancer treatments. However, most patients still fail to respond to these therapies. The molecular determinants of immune resistance are poorly understood. We show that loss of PTEN in tumor cells in preclinical models of melanoma inhibits T cell-mediated tumor killing and decreases T cell trafficking into tumors. In patients, PTEN loss correlates with decreased T cell infiltration at tumor sites, reduced likelihood of successful T cell expansion from resected tumor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

46
1,055
5
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,253 publications
(1,160 citation statements)
references
References 54 publications
46
1,055
5
5
Order By: Relevance
“…We did note that the expression levels of HLA class I genes (HLA-A, -B, -C) trended higher among the responding tumors, although the differences were not statistically significant. Lastly, the complete loss of PTEN was reported to promote resistance to immune checkpoint blockade (Peng et al, 2015), but there was only one case of homozygous PTEN deletion (with nearly undetectable PTEN mRNA expression; Figure S2A) in our cohort (in the nonresponsive sub-group), limiting our ability to draw meaningful associations in this dataset. Generally, we did not observe a statistically significant difference in PTEN expression between anti-PD-1 responding versus non-responding tumors.…”
Section: Co-enriched Transcriptomic Signatures In a Major Subset Of Amentioning
confidence: 92%
See 1 more Smart Citation
“…We did note that the expression levels of HLA class I genes (HLA-A, -B, -C) trended higher among the responding tumors, although the differences were not statistically significant. Lastly, the complete loss of PTEN was reported to promote resistance to immune checkpoint blockade (Peng et al, 2015), but there was only one case of homozygous PTEN deletion (with nearly undetectable PTEN mRNA expression; Figure S2A) in our cohort (in the nonresponsive sub-group), limiting our ability to draw meaningful associations in this dataset. Generally, we did not observe a statistically significant difference in PTEN expression between anti-PD-1 responding versus non-responding tumors.…”
Section: Co-enriched Transcriptomic Signatures In a Major Subset Of Amentioning
confidence: 92%
“…In addition to mesenchymal genes, genes associated with wound healing and angiogenesis, which are considered T cell-suppressive (Motz and Coukos, 2011;Schafer and Werner, 2008;Voron et al, 2014), were expressed higher among non-responding relative to responding pretreatment tumors. Interestingly, a recent study using a mouse melanoma model showed that VEGFA and CCL2 expression was associated with innate anti-PD-1 resistance (Peng et al, 2015). CDH1, which is typically down-expressed by mesenchymal cancer cells, was also downexpressed by non-responding (versus responding) pretreatment tumors.…”
Section: Co-enriched Transcriptomic Signatures In a Major Subset Of Amentioning
confidence: 99%
“…Recent work has pointed toward several additional tumor-intrinsic oncogene pathways that are associated with immune exclusion and are also ripe for targeting. These include the PTEN/PI3K pathway [120] in melanoma, the FGFR3 pathway in bladder cancer [121], and c-myc in hematologic malignancies [122]. As an exhaustive analysis of additional molecular pathways is collated through analysis of TCGA and other ongoing prospective genomic studies of samples in the context of immunotherapy clinical trials, it is expected that a prioritized list of candidate drug targets will emerge.…”
Section: Therapeutic Opportunitiesmentioning
confidence: 99%
“…PTENdeficient carcinoma cells may evade immune responses this way, and the loss of PTEN promotes resistance to T-cellmediated immunotherapy, including the use of anti-PD-1. 61,62 Moreover, cytokines may affect PTEN functions. For instance, transforming growth factor-β (TGF-β) was shown to induce the loss of PTEN enzymatic activity by phosphorylating the C terminus of PTEN, and tumor necrosis factor-α (TNF-α) has been shown to increase the expression of PTEN.…”
Section: Functions Of Tumor Suppressor Pten L Chen and D Guomentioning
confidence: 99%